Germ tube formation changes surface hydrophobicity of Candida cells. - Rodrigues, A G (1999)
Hydrophobic interaction is generally considered to play an important role in the adherence of microorganisms to eukaryotic cells and also to certain inert surfaces. Using a microbe adhesion assay to hydrocarbons (n-hexadecane), 68 strains of Candida albicans and 30 non-albicans strains were studied. Influence of source of isolate, age of the culture, and percentage of germ tube formation on adhesion were studied. C. albicans blastoconidia were found to be hydrophilic; conversely, blastoconidia of non-albicans strains were slightly more hydrophobic. Germ tube formation was associated with a significant rise in cell surface hydrophobicity.